Sharia Banking Syndicated Financing in The Context of Funding Strategic Projects after Islamic Financial Qanun Institution in Aceh - Nurhisam, Luqman; Eriyanti, Nahara; Mundakir, Mundakir; Mursid, Fadillah; Khulwah, Juhrotul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
This article focus on Islamic banking syndicated financing in the context of funding strategic projects in Aceh Province after the enactment of Qanun Number 11 of 2018. The research methodology used is normative legal study, which includes analysis of norms, principles of Islamic banking, and opinions of Islamic economic law experts. The approaches employed are the legislative approach. The object of this research is focused on the role of Islamic banks and the mechanisms carried out by Islamic banking in syndicated financing after the establishment of Qanun Number 11 of 2018 concerning Islamic Financial Institutions. The results of this study indicate that in the context of funding strategic projects, the infrastructure development of Aceh Province. That Islamic banking syndicated financing has an important role on the basis of financing needs on a large scale. It is hoped that the syndicated financing will be the right solution by referring to several provisions that contain sharia principles in the sharia banking syndicated financing process. The enactment of Qanun Number 11 of 2018 concerning Islamic Financial Institutions, became the legal basis for the implementation of syndicated financing. In addition, it also refers to the fatwa issued by DSN-MUI Number 91/DSN-MUI/IV/2014 concerning Syndicated Financing (Al-Tamwil Al-Mashrifi Al-Mujamma'), and based on OJK Circular Letter No. 36/SEOJK.03/ 2015 concerning Products and Activities of Islamic Commercial Banks and Sharia Business Units. So the implementation of syndicated financing at Islamic banks in Indonesia is in principle in line with the existing provisions in Sharia, but still must continue to be supervised by the Sharia Supervisory Board/DPS in this case the context is the Aceh Sharia Council/DSA so that there are no violations in its implementation.